Exaptation and language change - Norde, Muriel, 1968-; Velde, Freek van de (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2016)
"This volume is the first collection of papers that is exclusively dedicated to the concept of exaptation, a notion from evolutionary biology that was famously introduced into linguistics by Roger Lass in 1990. The past quarter-century has seen a heated debate on the properties of linguistic exaptation, its demarcation from other processes of linguistic change, and indeed the question of whether it is a useful concept in historical linguistics at all. The contributions in the present volume reflect these diverging points of view. Along with a comprehensive introduction, covering the history of the notion of exaptation from its conception in the field of biology to its adoption in linguistics, the book offers extensive discussion of the concept from various theoretical perspectives, detailed case studies as well as critical reviews of some stock examples. The book will be of interest to scholars working in the fields of evolutionary linguistics, historical linguistics, and the history of linguistics."--